Word stress : theoretical and typological issues - Hulst, Harry van der (Cambridge : Cambridge University Press, 2014)
Word stress has long presented challenges to phonologists, as they have sought to uncover patterns in its distribution, and devise models to account for its behaviour and formal representation both within single languages and cross-linguistically. In this collection, a team of world-renowned researchers present a variety of viewpoints on the methods and problems involved. Offering fresh perspectives on the topic and its study, this book is specifically concerned with basing theoretical work on broad typological surveys and focuses on the collection, selection and use of data in the analysis of word stress and word rhythm, including their phonetic manifestations. An extensive introduction presents a state-of-the-art review of stress research. The contributors also present StressTyp2, a project in an advanced stage of development, which intends to make publicly available information on word stress in a broad sample of languages and will offer new ways of understanding this key research area.
Part I. The Phenomenon of Stress: 1. The study of word accent and stress: past, present and future / Harry van der Hulst; 2. Do all languages have word accent? / Larry M. Hyman; 3. Disentangling stress and pitch accent: a typology of prominence at different prosodic levels / Matthew Gordon; 4. The separation of accent and rhythm: evidence from StressTyp / Rob Goedemans and Harry van der Hulst -- \ Part II. The Description, Selection and Use of Stress Data: 5. Evaluating evidence for stress systems . Paul de Lacy; 6. Convergence of prominence systems? / Keren Rice; 7. Rhetorical stress in Spanish / José I. Hualde and Marianna Nadeu -- Part III. The Analysis of Stress Types/Stress Phenomena: 8. Culminativity times harmony equals unbounded stress / Jeffrey Heinz; 9. Possible and impossible exceptions in Dutch word stress / Carlos Gussenhoven; 10. Symmetries and asymmetries in secondary stress patterns / Brett Hyde; 11. Representing rhythm / Harry van der Hulst.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Grammar, Comparative and general -- Phonology; Linguistics